A bírósági végrehajtási eljárás cselekményeinek láncolatát átmenetileg megakasztó jogintézmények - Gyüre, Péter (Debreceni Jogi Műhely, 2018)
This study presents the legal institutions that temporarily interrupt the chain of procedural actions of the judicial foreclosure, namely the interruption, suspension and intermission of the foreclosure. In the publication - as an acting lawyer - pragmatism has an emphasised role and it highlights the problems that arise when applying the legal institutions and offers alternatives and de lege ferenda solutions. The author seeks to draw the reader's attention to the interrelations and differences between legal institutions for the sake of clarity. Furthermore the speciality of this study is that it uses the civil procedural regulations which are applicable as a background standard for the Code of Judicial Foreclosure, from the new Code of Civil Procedure which entered into force on 1 January 2018, referring in several places simultaneously to the regulations of the previous CCP.